Aquaculture value chain performance - Ali, Hazrat; Belton, Ben; Khondker, Murshed-E-Jahan; Hernández, Ricardo; Haque, M Mahfujul (2022)
The aquaculture value chain performance survey was conducted with 1195 actors including 721 fish farm households, 66 fish hatcheries, 79 fish feed traders and 329 fish traders in south and southwest regions of Bangladesh